2015
DOI: 10.1007/s12325-015-0256-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Factors Associated with Non-Adherence to Treatment for Immune-Mediated Inflammatory Diseases

Abstract: BackgroundNon-adherence impacts negatively on patient health outcomes and has associated economic costs. Understanding drivers of treatment adherence in immune-mediated inflammatory diseases is key for the development of effective strategies to tackle non-adherence.ObjectiveTo identify factors associated with treatment non-adherence across diseases in three clinical areas: rheumatology, gastroenterology, and dermatology.DesignSystematic review.Data SourcesArticles published in PubMed, Science Direct, PsychINFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 92 publications
(110 reference statements)
11
124
0
3
Order By: Relevance
“…This may be a reflection of access to advanced therapies in the EU5, with public insurance coverage being more prominent compared with the US healthcare systems. A recent systematic review of medication adherence in patients with a range of conditions, including PsA, identified varying levels of non-adherence, which can impact negatively on health outcomes and have associated economic costs [49]. In the systematic review, psychosocial factors, such as perceived treatment efficacy and safety, emotional well-being, HCP–patient relationship, and practical barriers, were shown to be key factors in determining patient adherence to treatment, while demographic and clinical factors showed less of an association with adherence [49].…”
Section: Discussionmentioning
confidence: 99%
“…This may be a reflection of access to advanced therapies in the EU5, with public insurance coverage being more prominent compared with the US healthcare systems. A recent systematic review of medication adherence in patients with a range of conditions, including PsA, identified varying levels of non-adherence, which can impact negatively on health outcomes and have associated economic costs [49]. In the systematic review, psychosocial factors, such as perceived treatment efficacy and safety, emotional well-being, HCP–patient relationship, and practical barriers, were shown to be key factors in determining patient adherence to treatment, while demographic and clinical factors showed less of an association with adherence [49].…”
Section: Discussionmentioning
confidence: 99%
“…This is why most SMDs must be taken daily or twice daily. However, long-term adherence to treatment with oral drugs is often poor in clinical practice and the best way to improve this is still being debated 41 42. Nevertheless, adherence to intravenously or subcutaneously administered anti-TNF therapeutics in IBD is not optimal either 43…”
Section: Small Molecules Versus Monoclonal Antibodiesmentioning
confidence: 99%
“…First, long-term adherence to other oral drugs used in IBD (such as azathioprine and aminosalicylates) is poor 42. Second, the SMDs' positioning will remain a matter of debate until head-to-head trials against monoclonal antibodies or between SMDs are performed.…”
Section: Perspectivesmentioning
confidence: 99%
“…Considering that patients with chronic disorders are less likely to be compliant with treatment regimen compared with those with acute conditions;31 non-adherence is one of the key factors in the real-life effectiveness of treatments for chronic disorders, such as psoriasis 32. Medication non-adherence can have harmful effects on optimal management of psoriasis: non-adherence leads to poor outcomes, more hospitalizations, and significantly higher health care costs 30,3335. Our findings are consistent with previous investigations36,37 that demonstrated a suboptimal adherence to topical treatments, likely reflecting the intermittent use of most topical products.…”
Section: Discussionmentioning
confidence: 99%